Effects of population density on life history traits in a moth: in search of proximate and ultimate explanations - Kerli Kuusk; Toomas Esperk; Tiit Teder; Sille Holm; Toomas Tammaru (Oecologia, 2026)

Beneath the blades: Marine wind farms support parts of local biodiversity - a systematic review - Alexander H. Knorrn; Tiit Teder; Ants Kaasik; Randel Kreitsberg (Science of The Total Environment, 2024)

Insect-pollinated plants are first to disappear from overgrowing grasslands: Implications for restoring functional ecosystems - Virve Sõber; Tsipe Aavik; Ants Kaasik; Meeli Mesipuu; Tiit Teder (Biological Conservation, 2024)

Ecologically-Informed Precision Conservation: A framework for increasing biodiversity in intensively managed agricultural landscapes with minimal sacrifice in crop production - Michal Knapp; Tiit Teder; Vojtěch Lukas; Martin Štrobl; Jana Knappová; Douglas A. Landis; Ezequiel González (Biological Conservation, 2023)

Landscape-level determinants of butterfly species richness in northern Europe: A country-wide survey reveals the paramount importance of forest land - Toomas Tammaru; Daniel Valdma; Anu Tiitsaar; Ants Kaasik; Erki Õunap; Jaanus Remm; Tiit Teder (Biological Conservation, 2023)

Early‐life food stress hits females harder than males in insects: A meta‐analysis of sex differences in environmental sensitivity - Tiit Teder; Ants Kaasik (Ecology Letters, 2023)
Fitness consequences of early‐life environmental conditions are often sex‐specific, but corresponding evidence for invertebrates remains inconclusive. Here, we use meta‐analysis to evaluate sex‐specific sensitivity to larval nutritional conditions in insects. Using literature‐derived data for 85 species with broad phylogenetic and ecological coverage, we show that females are generally more sensitive to food stress than males. Stressful nutritional conditions during larval development typically lead to female‐biased mortality and thus increasingly male‐biased sex ratios of emerging adults. We further demonstrate that the general trend of higher sensitivity to food stress in females can primarily be attributed to their typically larger body size in insects and hence higher energy needs during development. By contrast, there is no consistent evidence of sex‐biased sensitivity in sexually size‐monomorphic species. Drawing conclusions regarding sex‐biased sensitivity in species with male‐biased size dimorphism remains to wait for the accumulation of relevant data. Our results suggest that environmental conditions leading to elevated juvenile mortality may potentially affect the performance of insect populations further by reducing the proportion of females among individuals reaching reproductive age. Accounting for sex‐biased mortality is therefore essential to understanding the dynamics and demography of insect populations, not least importantly in the context of ongoing insect declines.

Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment - Gustavo Q. Romero; Thiago Gonçalves‐Souza; Tomas Roslin; Robert J. Marquis; Nicholas A.C. Marino; Vojtech Novotny; Tatiana Cornelissen; Jerome Orivel; Shen Sui; Gustavo Aires; Reuber Antoniazzi; Wesley Dáttilo; et al. (Global Change Biology, 2022)
Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11,790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls’ effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Invasive host caught up with a native parasitoid: field data reveal high parasitism of Harmonia axyridis by Dinocampus coccinellae in Central Europe - Michal Knapp; Michal Řeřicha; Sarah Maršíková; Filip Harabiš; Tomáš Kadlec; Oldřich Nedvěd; Tiit Teder (Biological Invasions, 2019)

Oviposition site selection of the Alcon blue butterfly at the northern range margin - Margus Vilbas; Toomas Esperk; Triin Edovald; Ants Kaasik; Tiit Teder (Journal of Insect Conservation, 2016)

Host ant use of the Alcon blue butterfly at the northern range margin - Margus Vilbas; Toomas Esperk; Tiit Teder (Journal of Insect Conservation, 2016)

Polyphagy on unpredictable resources does not exclude host specialization: insects feeding on mushrooms - Kadri Põldmaa; Ants Kaasik; Toomas Tammaru; Olavi Kurina; Siiri Jürgenstein; Tiit Teder (Ecology, 2016)
The degree of ecological specialization plays a crucial role in shaping the structure and functioning of communities. However, comparing specialization within and among groups of organisms is complicated by both methodological issues and conceptual and terminological inconsistencies. Environmental predictability has been considered a key determinant of specialization though empirical evidence is still limited. Fungi and their insect consumers provide a poorly studied but promising system to measure host specialization and test the predictability hypothesis. In this study, we systematically sampled mushrooms in North European boreal forest, and reared total samples of fungivores colonizing the fruitbodies. Due to the unpredictable nature of mushrooms as a resource, low levels of host specialization can be predicted for these insects, which have indeed widely been considered polyphagous. Contrary to expectations, the majority of the studied fungus gnats were found not to exploit their host taxa indiscriminately. Not only were some mushroom taxa never colonized, the infestation rate of acceptable hosts also differed in most of these fungivores. Gnat species themselves formed continua with respect to the estimates of the degree of specialization, derived from parametric individual‐based analyses of presence‐absence data. In most cases, host use was best explained by models in which the hosts were classified at genus level, with limited support to specialization to particular host species, families, or orders. Indeed, most of the common fungivores appeared to preferentially use various species from one or a few mushroom genera while occasionally feeding on members of other host taxa. This pattern has likely evolved as a compromise between selective forces stemming from host unpredictability and taxon‐specific chemical profiles of the mushrooms. Our study highlights the multidimensional nature of ecological specialization: a high number of acceptable hosts does not preclude considerable discrimination among members of the available resource pool. Such situations can only be revealed by individual‐based analyses capable of capturing differences in partner‐to‐partner interaction intensities.

Distinguishing between anticipatory and responsive plasticity in a seasonally polyphenic butterfly - Toomas Esperk; Constanti Stefanescu; Tiit Teder; Christer Wiklund; Ants Kaasik; Toomas Tammaru (Evolutionary Ecology, 2013)

The effects of seasonally variable dragonfly predation on butterfly assemblages - Anu Tiitsaar; Ants Kaasik; Tiit Teder (Ecology, 2013)
Where predation is seasonally variable, the potential impact of a predator on individual prey species will critically depend on phenological synchrony of the predator with the prey. Here we explored the effects of seasonally variable predation in multispecies assemblages of short‐lived prey. The study was conducted in a landscape in which we had previously demonstrated generally high, but spatially and seasonally variable dragonfly‐induced mortality in adult butterflies. In this system, we show that patterns of patch occupancy in butterfly species flying during periods of peak dragonfly abundance are more strongly associated with spatial variation in dragonfly abundance than patch occupancy of species flying when dragonfly density was low. We provide evidence indicating that this differential sensitivity of different butterfly species to between‐habitat differences in dragonfly abundance is causally tied to seasonal variation in the intensity of dragonfly predation. The effect of dragonfly predation could also be measured at the level of whole local butterfly assemblages. With dragonfly density increasing, butterfly species richness decreased, and butterfly species composition tended to show a shift toward a greater proportion of species flying during periods of off‐peak dragonfly abundance.

Why is body size more variable in stressful conditions: an analysis of a potential proximate mechanism - Toomas Tammaru; Tiit Teder (Evolutionary Ecology, 2012)

Habitat fragmentation causes immediate and time‐delayed biodiversity loss at different trophic levels - Jochen Krauss; Riccardo Bommarco; Moisès Guardiola; Risto K. Heikkinen; Aveliina Helm; Mikko Kuussaari; Regina Lindborg; Erik Öckinger; Meelis Pärtel; Joan Pino; Juha Pöyry; Katja M. Raatikainen; et al. (Ecology Letters, 2010)
Ecology Letters (2010) 13: 597–605 Abstract Intensification or abandonment of agricultural land use has led to a severe decline of semi‐natural habitats across Europe. This can cause immediate loss of species but also time‐delayed extinctions, known as the extinction debt. In a pan‐European study of 147 fragmented grassland remnants, we found differences in the extinction debt of species from different trophic levels. Present‐day species richness of long‐lived vascular plant specialists was better explained by past than current landscape patterns, indicating an extinction debt. In contrast, short‐lived butterfly specialists showed no evidence for an extinction debt at a time scale of c. 40 years. Our results indicate that management strategies maintaining the status quo of fragmented habitats are insufficient, as time‐delayed extinctions and associated co‐extinctions will lead to further biodiversity loss in the future.

Counterintuitive size patterns in bivoltine moths: late-season larvae grow larger despite lower food quality - Tiit Teder; Toomas Esperk; Triinu Remmel; Anu Sang; Toomas Tammaru (Oecologia, 2010)

Proximate sources of sexual size dimorphism in insects: locating constraints on larval growth schedules - Toomas Tammaru; Toomas Esperk; Vitali Ivanov; Tiit Teder (Evolutionary Ecology, 2010)

Monitoring of Biological Diversity: a Common‐Ground Approach - TIIT TEDER; MARI MOORA; ELLE ROOSALUSTE; KRISTJAN ZOBEL; MEELIS PÄRTEL; URMAS KÕLJALG; MARTIN ZOBEL (Conservation Biology, 2007)
Practical approaches to monitoring biological diversity vary widely among countries, and the accumulating data are frequently not generalizable at the international scale. Although many present monitoring schemes, especially in developed countries, produce highly complex data, there is often a lack of basic data about the level and spatial distribution of biodiversity. We augmented the general framework for improving biomonitoring, proposed by , and identified its core tasks and attributes. The first priority for a more unified biodiversity monitoring is to agree on a minimum set of core tasks and attributes, which will make it possible to build a standardized biomonitoring system even in countries with few resources. Our scheme has two main organizational levels—taxa and ecosystems. The basic elements of the biomonitoring system proposed are recording of presence and absence of taxa and ecosystems in a target area, mapping of their distribution in space, and assessment of their status. All the elements have to be repeated over time. Although these tasks are fundamental, they are frequently not considered in currently functioning biomonitoring programs. The whole system has to be hierarchical and additive: if more resources are available, new activities may be added to the basic routine. Agreeing on a common standard will facilitate aggregating measures of biodiversity status and trends into regional and global indices. This information will relate directly to several Convention on Biological Diversity indicators for assessing progress toward the 2010 Biodiversity Target.